Composite material for high-barrier food packaging and preparation method thereof

By designing a three-layer composite structure, including polyamide, nano-siloxane, and metallocene polyethylene layers, the problem of brittleness at low temperatures and interlayer delamination in acidic environments of nylon/polyethylene composite films is solved, achieving high barrier properties and durability for high-moisture acidic foods in cold chain transportation.

CN120863183AActive Publication Date: 2025-10-31SICHUAN PROVINCE XINDU YONGZHI PRINTING CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202511378297.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-25
Publication Date
2025-10-31
Estimated Expiration
2045-09-25

AI Technical Summary

Technical Problem

Existing nylon/polyethylene (PA/PE) composite films become more brittle at low temperatures, and vibrations during transportation can easily cause the seals to crack. In high humidity and acidic environments, moisture absorption and swelling can lead to interlayer delamination, making them unable to meet the impact resistance requirements for long-distance transportation of high-moisture, acidic foods.

Method used

It adopts a three-layer composite structure, including a substrate layer, an acid-resistant layer and a heat-sealing layer. The substrate layer is composed of polyamide and nano-siloxane layers. The acid-resistant layer prevents acidic water vapor from penetrating through chemical bonding. The heat-sealing layer uses a metallocene polyethylene layer to maintain low-temperature flexibility. Combined with a titanium layer and a nano-silica layer, the barrier performance is enhanced.

Benefits of technology

It effectively improves the barrier properties of traditional materials in acidic and humid environments, reduces the rate of bag breakage during cold chain transportation, and extends the shelf life of food.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a composite material for high-barrier food packaging and a preparation method thereof, and belongs to the technical field of food packaging. The high-barrier composite material for food packaging comprises a base material layer, an acid-resistant layer and a heat sealing layer, the base material layer comprises a polyamide layer and a nano siloxane layer positioned on at least one surface of the polyamide layer; the acid-resistant layer is positioned between the base material layer and the heat sealing layer and is used for preventing interlayer separation caused by permeation of acidic water vapor; and the heat sealing layer comprises a metallocene polyethylene layer. The high-barrier composite material for food packaging can effectively relieve the problems of low-temperature brittleness and damage of an acid medium to a composite film, has high barrier property and low-temperature resistance, and is beneficial to reducing the bag breaking rate of packaging and prolonging the preservation period of high-moisture acid food in cold-chain transportation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of food packaging technology, specifically relating to a high-barrier food packaging composite material and its preparation method. Background Technology

[0002] In the industrial packaging and transportation of high-moisture, acidic foods, preservation is the core requirement. Packaging materials must have excellent impact resistance and high barrier properties in low-temperature storage and transportation environments to prevent bag breakage and maintain a shelf life of more than 6 months, ensuring that the food does not leak or deteriorate in the vibration, high humidity and acidic media during transportation.

[0003] However, existing technologies mainly rely on traditional nylon / polyethylene (PA / PE) composite films or their variants, which suffer from conflicting material properties and difficult-to-overcome process bottlenecks. The low-temperature crystallization of traditional nylon / polyethylene (PA / PE) composite films leads to a significant increase in brittleness, making them prone to edge cracking and leakage due to transport vibrations. This risk is particularly pronounced in large-capacity packaging (5kg and above), failing to meet the impact resistance requirements for long-distance transport of high-moisture, acidic foods. Simultaneously, the nylon substrate layer absorbs moisture and swells in high humidity (>85% RH) and acidic (pH≤4) environments, causing interlayer delamination in the composite material and increasing water vapor permeability, thus accelerating food spoilage. These contradictions prevent existing technologies from balancing low-temperature toughness, acidic environment barrier properties, and production efficiency, necessitating breakthroughs through material innovation and process synergy. Summary of the Invention

[0004] The purpose of this application is to provide a high-barrier food packaging composite material and its preparation method. This high-barrier food packaging composite material can effectively alleviate the problems of low-temperature brittleness and acidic media damage to the composite film. It has high barrier properties and low-temperature resistance, which is beneficial for reducing the bag breakage rate and extending the shelf life of high-moisture acidic foods during cold chain transportation.

[0005] In a first aspect, this application provides a high-barrier food packaging composite material, comprising a substrate layer, an acid-resistant layer, and a heat-sealing layer; the substrate layer comprises a polyamide layer and a nano-siloxane layer located on at least one surface of the polyamide layer; the acid-resistant layer is located between the substrate layer and the heat-sealing layer, used to prevent interlayer separation caused by the penetration of acidic moisture; the heat-sealing layer comprises a metallocene polyethylene layer. This application adopts a three-layer composite structure, with the polyamide in the substrate layer providing a mechanical support base, which, together with the surface nano-siloxane layer, forms a dense inorganic barrier, improving the barrier efficiency against gases such as oxygen, and mitigating the low-temperature brittleness and moisture absorption swelling problems of polyamide; the middle acid-resistant layer is specifically designed for acidic moisture penetration, intercepting the hydrogen ion migration path through chemical bonding, effectively preventing the acidity of the contents from corroding the material; the heat-sealing layer uses metallocene polyethylene, which, by leveraging its highly regular molecular chain characteristics, maintains excellent heat-sealing strength and flexibility at low temperatures. This composite structure, through the close cooperation of its components, effectively improves the problem of the degradation of the barrier performance of traditional materials in acidic and humid environments. At the same time, it alleviates the embrittlement of the heat-sealing layer under cold chain conditions, which is beneficial for reducing the bag breakage rate and extending the shelf life of high-moisture acidic foods during cold chain transportation.

[0006] Preferably, the acid-resistant layer comprises a polyurethane-nano silica composite layer or a polyvinylidene chloride-maleic anhydride graft composite layer; the polyurethane-nano silica composite layer comprises polyurethane and nano silica; based on the mass of the polyurethane-nano silica composite layer, the mass percentage of nano silica is 0.5-2%; the polyvinylidene chloride-maleic anhydride graft composite layer comprises a polyvinylidene chloride copolymer, the polyvinylidene chloride copolymer contains maleic anhydride grafts, and the grafting rate of the maleic anhydride grafts is 1.2-1.8%. This application provides two options: a polyurethane-nano silica composite layer or a polyvinylidene chloride-maleic anhydride grafted composite layer. The polyurethane-nano silica composite layer utilizes the uniform dispersion of nano silica within the polyurethane matrix and controls the mass percentage of nano silica to fill micropores and extend the penetration path of acidic moisture, thereby enhancing barrier efficiency and anti-swelling properties. The polyvinylidene chloride-maleic anhydride grafted composite layer, through maleic anhydride grafting modification, introduces polar groups to strengthen intermolecular forces, improving the interfacial bonding strength with the substrate layer while maintaining high barrier properties, thus preventing interlayer peeling and migration failure caused by acidic media. When the grafting rate of maleic anhydride grafts is 1.2~1.8%, a peel strength ≥4.5 N / 15 mm can be achieved. Both composite layers effectively reduce the risk of cracking under dynamic stress and the probability of permeation failure during long-term storage, thereby improving the protective effect of packaging in corrosive environments and extending the shelf life of food.

[0007] Preferably, the polyurethane includes fluorinated polyurethane; the mass percentage of fluorine in the polyurethane is 1.5-2%. The strong CF bonds formed after the introduction of fluorine atoms into the fluorinated polyurethane can improve the chemical inertness of the molecular chain, effectively reducing the erosion of acidic moisture and minimizing material swelling or degradation caused by hydrogen ion penetration. Controlling the fluorine content to meet the above range can optimize surface energy properties, avoid processing difficulties or embrittlement risks caused by excessively high fluorine content, and help reduce the packaging breakage rate and extend the shelf life of high-moisture acidic foods during cold chain transportation.

[0008] Preferably, the porosity of the nano-siloxane layer is <0.3%, and the mass percentage of silicon in the nano-siloxane layer is ≥25%. Low porosity can reduce microscopic pore defects and inhibit the diffusion rate of acidic water vapor (such as acetic acid vapor), enhancing physical barrier efficiency. High silicon content forms a dense molecular-level barrier by increasing the cross-linking density of the siloxane network, effectively reducing hydrogen ion erosion and maintaining structural stability under long-term acidic environments. This is beneficial for reducing the packaging breakage rate and extending the shelf life of high-moisture acidic foods during cold chain transportation.

[0009] Preferably, a titanium layer is further included between the substrate layer and the acid-resistant layer; the thickness of the titanium layer is 2~10 nm. As an inert metal, the titanium layer's chemical stability effectively inhibits the penetration of acidic moisture and reduces the erosion of the interlayer interface by hydrogen ions. By controlling the titanium layer thickness within the aforementioned preferred range, interlayer adhesion can be optimized, and molecular-level interactions can be enhanced, thereby preventing interlayer delamination under dynamic stress or acidic environments and maintaining the long-term reliability of the overall packaging structure. This enables the cross-cut test of the composite material for food packaging to reach the 0-level standard, effectively alleviating the problems of low-temperature brittleness and acidic media damage to the composite film, and is beneficial for reducing the bag breakage rate and extending the shelf life of high-moisture acidic foods during cold chain transportation.

[0010] Preferably, the heat-sealing layer includes heat-sealing layer A and heat-sealing layer B; heat-sealing layer A is located between heat-sealing layer B and acid-resistant layer; heat-sealing layer A includes a metallocene-catalyzed ethylene-hexene copolymer, and heat-sealing layer B includes an ethylene-octene copolymer; in the heat-sealing layer, the mass percentage of hexene is 84-87%, and the mass percentage of octene is 12-15%. Designing the heat-sealing layer as a double-layer structure of heat-sealing layer A and heat-sealing layer B can improve the heat-sealing reliability and functionality of the composite packaging. Heat-sealing layer A (metallocene-catalyzed ethylene-hexene copolymer), located between the acid-resistant layer and heat-sealing layer B, can enhance interlayer adhesion and buffer stress transmission, reducing the risk of interface peeling. By controlling the mass percentage of octene within the above range, the heat-sealing layer can optimize the flexibility and crystallinity of the copolymer chain, providing low-temperature heat-sealing strength and impact resistance, ensuring the integrity of the sealing interface in an acidic environment, which is beneficial for reducing the packaging breakage rate and extending the shelf life of high-moisture acidic foods during cold chain transportation. In addition, by controlling the mass ratio of octene to 12-15%, the strength of the heat-sealing layer can be improved, so that the right-angle tear strength of the composite material for food packaging at -40℃ is ≥120 kN / m.

[0011] Preferably, the thickness of the substrate layer is 12~30μm, the thickness of the acid-resistant layer is 1~6μm, and the thickness of the heat-sealing layer is 80~120μm.

[0012] Secondly, this application also provides a method for preparing the above-mentioned high-barrier food packaging composite material, including the following steps: Step S1, a polyamide layer is chemically vapor-deposited in a silane / oxygen mixed atmosphere to form a SiOx layer, where 1.8 ≤ x ≤ 2.1; then a polyvinyl alcohol solution of silane coupling agent is coated onto the SiOx layer for organosiloxane modification treatment to obtain a substrate layer; Step S2, an acid-resistant liquid is coated onto the surface of the substrate layer to form an acid-resistant layer on the surface of the substrate layer; Step S3, a heat-sealing layer is composited onto the surface of the acid-resistant layer by co-extrusion to obtain the high-barrier food packaging composite material. This application employs chemical vapor deposition (CVD) in a silane / oxygen mixed atmosphere to form a SiOx layer (1.8 ≤ x ≤ 2.1). The vacuum deposition process ensures a uniform, dense, and controllable SiOx layer. A polyvinyl alcohol solution coated with a silane coupling agent enhances the interfacial compatibility and adhesion of the substrate layer, preventing interlayer delamination and improving overall structural stability. An acid-resistant layer formed by coating with an acid-resistant solution effectively blocks acidic moisture penetration and inhibits corrosive media from eroding the substrate, thereby improving the long-term durability of the packaging in acidic food environments. A co-extrusion composite heat-sealing layer enhances the interlayer thermal adhesion strength and sealing integrity. This application effectively alleviates the problems of low-temperature brittleness and acidic media damage to the composite film, which is beneficial for reducing the packaging breakage rate and extending the shelf life of high-moisture acidic foods during cold chain transportation.

[0013] Preferably, when the acid-resistant layer comprises a polyurethane-nano silica composite layer, the acid-resistant liquid comprises polyurethane and nano silica; based on the mass of the acid-resistant liquid, the mass percentage of nano silica is 0.6~1.5%; the particle size of the nano silica is 15~40nm; and the coating amount of the acid-resistant liquid is 1~1.6g / m². 2 The acid-resistant coating process involves micro-gravure roller coating followed by sequential heat treatment at 90-100℃, 100-110℃, and 110-120℃, with each temperature range requiring 1-2.0 seconds of heat treatment. This heat treatment forms an acid-resistant layer. By adjusting the preparation parameters of the polyurethane-nano silica composite layer to meet the above range, the coating's barrier efficiency against acidic moisture and its anti-swelling properties are effectively enhanced. Gradual heating promotes the full completion of the polyurethane cross-linking reaction, achieving a cross-linking degree of 75-80%. Simultaneously, optimized nanoparticle interface bonding ensures structural density and long-term chemical stability, which is beneficial for reducing the packaging breakage rate and extending the shelf life of high-moisture acidic foods during cold chain transportation.

[0014] Preferably, when the acid-resistant layer comprises a polyvinylidene chloride-maleic anhydride graft composite layer, the acid-resistant liquid comprises a polyvinylidene chloride copolymer; the solid content of the acid-resistant liquid is 18-28%; and the coating amount of the acid-resistant liquid is 3.2-4.5 g / m². 2 The acid-resistant coating process includes: reverse roller coating, followed by sequential heat preservation and curing treatments at 80-90℃ and 90-100℃, with each temperature range requiring 1-3 seconds of heat preservation. After heat preservation and curing, a composite treatment is performed at 80-90℃, 0.4-0.6MPa, and 300-400m / min to form an acid-resistant layer. By adjusting the preparation parameters of the polyvinylidene chloride-maleic anhydride graft composite layer to meet the above range, the performance stability and reliability of the acid-resistant layer in acidic environments can be effectively improved. The reverse roller coating process promotes the orderly arrangement of polyvinylidene chloride molecular chains and the interfacial reaction of maleic anhydride groups. Subsequent composite roller treatment further enhances the coating density and interlayer adhesion, which is beneficial for reducing the packaging breakage rate and extending the shelf life of high-moisture acidic foods during cold chain transportation.

[0015] Preferably, the volume ratio of silane gas to oxygen in the silane / oxygen mixed atmosphere is 1:(2~4); the deposition pressure of chemical vapor deposition is 60~120 Pa, and the radio frequency power is 300~800 W; SiO x The thickness of the layer is 200~300nm.

[0016] Preferably, the chemical vapor deposition is plasma-enhanced chemical vapor deposition. The plasma enhancement conditions include: in an Ar / O2 mixed gas, a temperature of 500~800℃, a plasma power of 200~400W, and a time of 1.5~5s, for example, a power of 300W and a time of 2s. After plasma enhancement, the surface energy of the substrate layer is increased to 50mN / m. In the Ar / O2 mixed gas, the volume ratio of Ar to O2 is 1:(2~5).

[0017] Preferably, the preparation method further includes: performing magnetron sputtering on the substrate layer to form a titanium layer, and then proceeding to step S2.

[0018] Preferably, a heat-sealing layer is composited onto the acid-resistant layer surface via co-extrusion, comprising: sequentially forming heat-sealing layer A and heat-sealing layer B on the acid-resistant layer surface by co-extruding a metallocene-catalyzed ethylene-hexene copolymer and an ethylene-octene copolymer, wherein the heat-sealing layer comprises heat-sealing layer A and heat-sealing layer B; heat-sealing layer A is located between heat-sealing layer B and the acid-resistant layer; the co-extrusion process includes: a temperature of 170~190℃ in zone 1 of the barrel, a temperature of 200~220℃ in zone 5 of the barrel, and a die temperature of 191~199℃. By controlling the temperature parameters of the co-extrusion process within the above range, the sealing reliability and impact resistance of the heat-sealing layer can be effectively improved, which is beneficial for reducing the bag breakage rate and extending the shelf life of high-moisture acidic foods during cold chain transportation.

[0019] This invention provides a high-barrier food packaging composite material, characterized in that it comprises a substrate layer, an acid-resistant layer, and a heat-sealing layer; The substrate layer includes a polyamide layer and a nano-siloxane layer located on at least one surface of the polyamide layer; The acid-resistant layer is located between the substrate layer and the heat-sealing layer to prevent interlayer separation caused by the penetration of acidic moisture. The heat-sealing layer includes a metallocene polyethylene layer.

[0020] In some embodiments, the acid-resistant layer includes a polyurethane-nano silica composite layer or a polyvinylidene chloride-maleic anhydride graft composite layer. The polyurethane-nano silica composite layer comprises polyurethane and nano silica; based on the mass of the polyurethane-nano silica composite layer, the mass percentage of nano silica is 0.5% to 2%. The polyvinylidene chloride-maleic anhydride grafted composite layer comprises a polyvinylidene chloride copolymer containing maleic anhydride grafts, wherein the grafting rate of the maleic anhydride grafts is 1.2~1.8%.

[0021] In some embodiments, the polyurethane includes fluorinated polyurethane; the mass percentage of fluorine in the polyurethane is 1.5-2%.

[0022] In some embodiments, the porosity of the nanosiloxane layer is <0.3%, and the mass percentage of silicon in the nanosiloxane layer is ≥25%.

[0023] In some embodiments, a titanium layer is further included between the substrate layer and the acid-resistant layer; the thickness of the titanium layer is 2~10nm.

[0024] In some embodiments, the heat-sealing layer includes heat-sealing layer A and heat-sealing layer B; heat-sealing layer A is located between heat-sealing layer B and the acid-resistant layer; The heat-sealing layer A comprises a metallocene-catalyzed ethylene-hexene copolymer, and the heat-sealing layer B comprises an ethylene-octene copolymer; in the heat-sealing layer, the mass percentage of hexene is 84-87%, and the mass percentage of octene is 12-15%.

[0025] In some embodiments, the thickness of the substrate layer is 12~30μm, the thickness of the acid-resistant layer is 1~6μm, and the thickness of the heat-sealing layer is 80~120μm.

[0026] The present invention also provides a method for preparing the above-mentioned high-barrier food packaging composite material, comprising the following steps: Step S1: The polyamide layer is subjected to chemical vapor deposition in a silane / oxygen mixed atmosphere to form SiO2. x Layer, 1.8≤x≤2.1; then to the SiO x A polyvinyl alcohol solution coated with a silane coupling agent is then subjected to organosiloxane modification treatment to obtain the substrate layer. Step S2: Apply an acid-resistant liquid to the surface of the substrate layer, and the acid-resistant liquid forms the acid-resistant layer on the surface of the substrate layer; Step S3: Apply the heat-sealing layer to the surface of the acid-resistant layer by co-extrusion to obtain the high-barrier food packaging composite material.

[0027] In some embodiments, when the acid-resistant layer comprises a polyurethane-nano silica composite layer, the acid-resistant liquid comprises polyurethane and nano silica; based on the mass of the acid-resistant liquid, the mass percentage of the nano silica is 0.6~1.5%; the particle size of the nano silica is 15~40nm. The coating amount of the acid-resistant solution is 1~1.6 g / m². 2 The acid-resistant coating process includes: coating with a micro-gravure roller, followed by heat preservation and curing treatment at 90~100℃, 100~110℃, and 110~120℃ in sequence, with a heat preservation time of 1~2.0s for each temperature range, and the acid-resistant layer is formed after the heat preservation and curing treatment.

[0028] In some embodiments, when the acid-resistant layer comprises a polyvinylidene chloride-maleic anhydride grafted composite layer, the acid-resistant liquid comprises the polyvinylidene chloride copolymer; the solid content of the acid-resistant liquid is 18-28%. The coating amount of the acid-resistant solution is 3.2~4.5 g / m². 2 The acid-resistant coating process includes: coating with a reverse roller, followed by a heat preservation and curing treatment at 90~100℃ and 110~120℃, with a heat preservation time of 1~3s for each temperature range; after the heat preservation and curing treatment, the coating is compounded at a temperature of 80~90℃, a pressure of 0.4~0.6MPa, and a speed of 300~400m / min to form the acid-resistant layer.

[0029] In some embodiments, in step S1, the volume ratio of silane gas to oxygen in the silane / oxygen mixed atmosphere is 1:(2~4); the deposition pressure of the chemical vapor deposition is 60~120 Pa, and the radio frequency power is 300~800 W; the SiO x The thickness of the layer is 200~300nm.

[0030] In some embodiments, the preparation method further includes: performing magnetron sputtering on the substrate layer to form a titanium layer, and then performing step S2.

[0031] In some embodiments, the step of applying the heat-sealing layer to the surface of the acid-resistant layer by co-extrusion includes: sequentially forming a heat-sealing layer A and a heat-sealing layer B on the surface of the acid-resistant layer by co-extrusion of a metallocene-catalyzed ethylene-hexene copolymer and an ethylene-octene copolymer, wherein the heat-sealing layer includes heat-sealing layer A and heat-sealing layer B; and heat-sealing layer A is located between heat-sealing layer B and the acid-resistant layer. The co-extrusion method includes: the temperature of zone 1 of the barrel is 170~190℃, the temperature of zone 5 of the barrel is 200~220℃, and the temperature of the die head is 191~199℃. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0033] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form a range not explicitly stated; and any lower limit can be combined with other lower limits to form a range not explicitly stated, just as any upper limit can be combined with any other upper limit to form a range not explicitly stated. Furthermore, although not explicitly stated, every point or individual value between the endpoints of the range is included within that range. Therefore, each point or individual value can be used as its own lower or upper limit and combined with any other point or individual value or with other lower or upper limits to form a range not explicitly stated.

[0034] The inventors discovered that packaging for high-moisture, acidic foods requires a balance between low-temperature impact resistance and high barrier properties (shelf life > 6 months). However, PA / PE films suffer from cold-chain brittleness and interlayer delamination due to acidic high humidity. The coating process for polyvinylidene chloride (PVDC) films requires extended low-temperature drying time to ensure uniform thickness, severely limiting production efficiency, and localized coating deviations still degrade barrier performance. For polyethylene films, improving low-temperature impact resistance requires increasing the content of polyethylene comonomers (such as octene), but this reduces thermal stability and conflicts with the high-temperature processing requirements of the nylon layer. Temperature imbalance in the co-extrusion die easily leads to heat-seal layer decomposition, making it impossible to simultaneously achieve peel strength and heat-seal performance.

[0035] To address the aforementioned issues, this application provides a high-barrier food packaging composite material, comprising a substrate layer, an acid-resistant layer, and a heat-sealing layer; the substrate layer comprises a polyamide layer and a nano-siloxane layer located on at least one surface of the polyamide layer; the acid-resistant layer is located between the substrate layer and the heat-sealing layer to prevent interlayer separation caused by the penetration of acidic moisture; the heat-sealing layer comprises a metallocene polyethylene layer. Specific Implementation

[0036] Example 1 Step S1: A 12 μm biaxially stretched PA6 film was used as the polyamide layer. One surface of the polyamide layer was subjected to plasma-enhanced chemical vapor deposition (PECVD) in a silane / oxygen mixture atmosphere with a flow rate ratio of 1:3. The plasma enhancement conditions included: an Ar / O2 mixed gas atmosphere (volume ratio 1:2), a temperature of 500 °C, a plasma power of 300 W, and a time of 2 s. The PECVD conditions included: a deposition pressure of 80 Pa, and the formation of 200 nm SiO2. x Dissolve 1000g of polyvinyl alcohol (PVA), add 5% KH560 (silane coupling agent), and stir until homogeneous; then add SiO2. xA polyvinyl alcohol solution containing 5% silane coupling agent KH560 is coated onto the polyamide layer for organosiloxane modification, forming a nano-siloxane layer. The same process is then repeated on the other surface of the polyamide layer to obtain the substrate layer. The substrate layer comprises the polyamide layer and nano-siloxane layers located on both surfaces of the polyamide layer. The porosity of the nano-siloxane layer is 0.1%, and the mass percentage of silicon in the nano-siloxane layer is 25%.

[0037] Step S2: First, magnetron sputtering is performed at 500W RF power to form a 2nm thick titanium transition layer. The acid-resistant solution is a polyurethane-nano silica (SiO2) composite system (wherein, the mass percentage of nano-SiO2 is 1%, and the particle size is 30nm). Microgravure roller coating is used (200 lines / inch), with a coating amount of 1.2g / m². 2 After coating, the material is cured in three stages at 90℃, 100℃, and 110℃, with a curing time of 1 second in each temperature range, forming a polyurethane-nano silica acid-resistant layer with a thickness of about 1μm.

[0038] Step S3: A heat-sealing layer is co-extruded onto the acid-resistant layer surface. A metallocene-catalyzed ethylene-hexene copolymer (ExxonMobil Exceed 2018) forms the metallocene polyethylene layer, i.e., heat-sealing layer A adjacent to the acid-resistant layer. An ethylene-octene copolymer (DowEngage 8180) forms heat-sealing layer B. In the heat-sealing layer, hexene accounts for 84-87% by mass, and octene accounts for 12-15% by mass. Co-extrusion parameters: barrel zone 1 temperature 180℃, barrel zone 5 temperature 210℃, die temperature 195℃, resulting in heat-sealing layer A with a thickness of 80μm and a total heat-sealing layer thickness of 120μm.

[0039] Example 2 The preparation method is similar to that in Example 1, except that: Step S2: The acid-resistant solution is a polyvinylidene chloride-maleic anhydride grafted composite system (wherein the maleic anhydride grafting rate is 1.5%), with a solid content of 22%; it is applied using a reverse roller coating with a coating amount of 3.8 g / m². 2 After coating, the material is subjected to two stages of heat preservation and curing at 90℃ and 100℃, with a heat preservation time of 1.2s for each temperature range. After heat preservation and curing, the material is subjected to composite treatment at 80℃, 0.4 MPa, and 300m / min to form an acid-resistant layer of polyvinylidene chloride-maleic anhydride graft with a thickness of 6μm.

[0040] Example 3 The preparation method is similar to that in Example 1, except that: Step S2: Fluorinated polyurethane is used instead of polyurethane, and the mass percentage of fluorine in the fluorinated polyurethane is 2%.

[0041] Example 4 The preparation method is similar to that in Example 1, except that: Step S2: Omit the preparation of the titanium layer.

[0042] Example 5 The preparation method is similar to that in Example 1, except that: Step S3: The heat-sealing layer B formed by the ethylene-octene copolymer (Dow Engage 8180) is omitted, that is, the heat-sealing layer only includes the metallocene polyethylene layer of the heat-sealing layer A.

[0043] Comparative Example 1 The preparation method is similar to that in Example 1, except that: Step S1: The preparation of the nano-siloxane layer is omitted, and the 12μm biaxially stretched PA6 film is directly used as the substrate layer.

[0044] Test case The packaging materials of each embodiment and comparative example were measured for water vapor transmission rate, -25°C dart impact test, 30-day peel strength after immersion in 4% acetic acid, and oxygen transmission rate (23°C). The water vapor transmission rate test involved cutting the composite film material to the dimensions of an oxygen-permeable mold and testing the water vapor transmission rate using an infrared detector according to GB / T 26253-2010, under conditions of 38°C and 90% Rh. The -25°C dart impact test involved freezing the composite film at -25°C for 24 hours, then quickly testing the impact strength using a dart impact tester. The 30-day peel strength test involved: 1. Preparing a 4% acetic acid aqueous solution; 2. Filling the bag made of the composite film with the acid solution; 3. Allowing it to stand at room temperature for 30 days; 4. Testing the peel strength using a tensile testing machine. The oxygen permeability test procedure includes cutting the composite membrane material to the dimensions of the oxygen permeability mold, and testing the oxygen permeability using the isobaric method according to GB / T 1038.2 Gas Permeability Test Method, under conditions of 23℃ and 50% Rh. The test results are shown in Table 1. Table 1 shows the test results.

[0045] As shown in Table 1, comparing Example 3 and Comparative Example 1, the high-barrier food packaging composite material obtained using the method of this application exhibits high barrier properties and low-temperature resistance, which is beneficial for reducing the bag breakage rate and extending the shelf life of high-moisture acidic foods during cold chain transportation. Furthermore, comparing Example 1 and Comparative Example 1 demonstrates the necessity of preparing the nano-siloxane layer in the method of this application. The nano-siloxane layer effectively blocks gases and acidic moisture, effectively mitigating the problems of low-temperature brittleness and damage to the composite film by acidic media, thus benefiting high-moisture acidic foods during cold chain transportation by reducing the bag breakage rate and extending the shelf life.

[0046] The difference between Example 1 and Example 3 is that Example 3 uses a fluorinated polyurethane acid-resistant layer. According to Table 1, the peel strength of Example 3 after soaking in 4% acetic acid for 30 days reached 5.1 N / 15mm, which is higher than that of Example 1 (4.2 N / 15mm). This indicates that the introduction of fluorine atoms can effectively reduce the erosion of acidic moisture. By controlling the mass ratio of fluorine in polyurethane to 1.5-2%, the surface energy characteristics can be optimized, which is beneficial for reducing the packaging breakage rate and extending the shelf life of high-moisture acidic foods during cold chain transportation.

[0047] As shown in Table 1, in Example 4, after omitting the titanium layer, the oxygen permeability is 0.6 cm. 3 / (m 2 • 24h), higher than 0.5 cm in Example 1 3 / (m 2 •24h) indicates that the titanium layer can effectively inhibit the penetration of acidic water vapor, effectively alleviate the problem of low-temperature brittleness and acidic medium damaging the composite film, and help reduce the packaging breakage rate and extend the shelf life of high-moisture acidic foods in cold chain transportation.

[0048] As shown in Table 1, the comparison between Example 1 and Example 5 demonstrates that the double-layer heat-sealing structure can further improve the heat-sealing reliability and functionality of the composite packaging, effectively alleviate the problems of low-temperature brittleness and acidic media damaging the composite film, and help reduce the bag breakage rate and extend the shelf life of high-moisture acidic foods during cold chain transportation.

[0049] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the principles of this application should be included within the protection scope of this application.

Claims

1. A high-barrier food packaging composite material, characterized in that, Includes a substrate layer, an acid-resistant layer, and a heat-sealing layer; The substrate layer includes a polyamide layer and a nano-siloxane layer located on at least one surface of the polyamide layer; The acid-resistant layer is located between the substrate layer and the heat-sealing layer to prevent interlayer separation caused by the penetration of acidic moisture. The heat-sealing layer includes a metallocene polyethylene layer.

2. The high-barrier food packaging composite material according to claim 1, characterized in that, The acid-resistant layer includes a polyurethane-nano silica composite layer or a polyvinylidene chloride-maleic anhydride graft composite layer. The polyurethane-nano silica composite layer comprises polyurethane and nano silica; based on the mass of the polyurethane-nano silica composite layer, the mass percentage of nano silica is 0.5% to 2%. The polyvinylidene chloride-maleic anhydride grafted composite layer comprises a polyvinylidene chloride copolymer containing maleic anhydride grafts, wherein the grafting rate of the maleic anhydride grafts is 1.2~1.8%.

3. The high-barrier food packaging composite material according to claim 2, characterized in that, The polyurethane includes fluorinated polyurethane; the mass percentage of fluorine in the polyurethane is 1.5-2%.

4. The high-barrier food packaging composite material according to claim 1, characterized in that, The porosity of the nanosiloxane layer is <0.3%, and the mass percentage of silicon in the nanosiloxane layer is ≥25%.

5. The high-barrier food packaging composite material according to claim 3, characterized in that, A titanium layer is also included between the substrate layer and the acid-resistant layer; the thickness of the titanium layer is 2~10nm.

6. The high-barrier food packaging composite material according to claim 1, characterized in that, The heat-sealing layer includes heat-sealing layer A and heat-sealing layer B; heat-sealing layer A is located between heat-sealing layer B and acid-resistant layer. The heat-sealing layer A comprises a metallocene-catalyzed ethylene-hexene copolymer, and the heat-sealing layer B comprises an ethylene-octene copolymer; in the heat-sealing layer, the mass percentage of hexene is 84-87%, and the mass percentage of octene is 12-15%.

7. The high-barrier food packaging composite material according to claim 1, characterized in that, The thickness of the substrate layer is 12~30μm, the thickness of the acid-resistant layer is 1~6μm, and the thickness of the heat-sealing layer is 80~120μm.

8. The method for preparing the high-barrier food packaging composite material according to any one of claims 1 to 7, characterized in that, Includes the following steps: Step S1: The polyamide layer is subjected to chemical vapor deposition in a silane / oxygen mixed atmosphere to form SiO2. x Layer, 1.8≤x≤2.1; then to the SiO x A polyvinyl alcohol solution coated with a silane coupling agent is then subjected to organosiloxane modification treatment to obtain the substrate layer. Step S2: Apply an acid-resistant liquid to the surface of the substrate layer, and the acid-resistant liquid forms the acid-resistant layer on the surface of the substrate layer; Step S3: Apply the heat-sealing layer to the surface of the acid-resistant layer by co-extrusion to obtain the high-barrier food packaging composite material.

9. The preparation method according to claim 8, characterized in that, When the acid-resistant layer includes a polyurethane-nano silica composite layer, the acid-resistant liquid includes polyurethane and nano silica; based on the mass of the acid-resistant liquid, the mass percentage of the nano silica is 0.6~1.5%; the particle size of the nano silica is 15~40nm. The coating amount of the acid-resistant solution is 1~1.6 g / m². 2 The acid-resistant coating process includes: coating with a micro-gravure roller, followed by heat preservation and curing treatment at 90~100℃, 100~110℃, and 110~120℃ in sequence, with a heat preservation time of 1~2.0s for each temperature range, and the acid-resistant layer is formed after the heat preservation and curing treatment.

10. The preparation method according to claim 8, characterized in that, When the acid-resistant layer comprises a polyvinylidene chloride-maleic anhydride grafted composite layer, the acid-resistant liquid comprises the polyvinylidene chloride copolymer; the solid content of the acid-resistant liquid is 18-28%. The coating amount of the acid-resistant solution is 3.2~4.5 g / m². 2 The acid-resistant coating process includes: coating with a reverse roller, followed by a heat preservation and curing treatment at 90~100℃ and 110~120℃, with a heat preservation time of 1~3s for each temperature range; after the heat preservation and curing treatment, the coating is compounded at a temperature of 80~90℃, a pressure of 0.4~0.6MPa, and a speed of 300~400m / min to form the acid-resistant layer.

Citation Information

Patent Citations

  • High-separation multilayer joint-extrusion shrink film

    CN102642359A

  • Polyurethane nanocomposites

    CN102686631A

  • High-barrier multi-layer coextrusion packaging film

    CN104999753A

  • High-barrier sauce packaging bag

    CN115648772A

  • Transparent high-barrier composite film and application

    CN117207632A